Role of Pessaries in the Treatment of Pelvic Organ Prolapse: A Systematic Review and Meta-analysis. Issue 4 (7th October 2022) - Sansone, Stephanie; Sze, Christina; Eidelberg, Andrew; Stoddard, Michelina; Cho, Ahra; Asdjodi, Saman; Mao, Jialin; Elterman, Dean S.; Zorn, Kevin C.; Chughtai, Bilal
Abstract : Pessaries are highly effective at improving the quality of life in women with pelvic organ prolapse. Abstract : OBJECTIVE: To evaluate the existing evidence on the efficacy of pessaries in improving quality of life when used for the treatment of pelvic organ prolapse (POP). DATA SOURCES: We searched for the terms "pelvic organ prolapse" and "pessar/y/ies/ium or vaginal support device, " and "safety or safe or outcome or complication or efficacy or effective or effectiveness" in PubMed, EMBASE, and CINAHL on March 16, 2020. A search was also performed on ClinicalTrials.gov, with no studies fitting our strict inclusion and exclusion criteria. METHODS OF STUDY SELECTION: Studies that reported pretreatment and posttreatment mean scores and SDs after pessary treatment for standardized questionnaires were included. Studies performed in pediatric populations, pregnancy, and use of pessaries not for prolapse were excluded. Three reviewers independently screened studies. TABULATION, INTEGRATION, AND RESULTS: Data abstraction was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were pooled for meta-analysis when reported by at least three studies. The primary study outcome was change in mean pretreatment and posttreatment questionnaire scores, which included those for the PFDI-20 (Pelvic Floor Distress Inventory- Short Form 20), PFIQ-7 (Pelvic Floor Impact Questionnaire - Short Form 7), and subscale POPIQ (Pelvic Organ Prolapse Impact Questionnaire Long Form). A random-effects model was used to combine estimates and capture between-study heterogeneity using the I 2 -statistic. Eight studies including 627 patients were included for systematic review. The mean (SD) age was 63.0±12.2 years, and the majority of patients had stage III prolapse (48.1%) followed by stage II prolapse (43.2%) when reported. Although variable, the majority of studies conducted 3-month follow-up. A negative change in pretreatment and posttreatment scores was noted, signifying improvement after pessary use: PFDI-20 mean change −46.1 (95% CI −65.4 to −26.8); PFIQ-7 mean change −36.0 (95% CI −46.0 to −26.0); POPIQ-7 (Pelvic Organ Prolapse Impact Questionnaire-7) mean change −16.3 (95% CI −26.8 to −5.7). No significant heterogeneity was found. CONCLUSION: Based on improvements in standardized questionnaire scores, pessaries are effective treatment options for POP. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020172618.